Mediterranean spotted fever and peripheral facial nerve palsy: a rare neurological complication. (April 2022) - Bouchaib, Hayet; Amrane, Achour; Sevestre, Jacques; Bitam, Idir; Parola, Phillipe
Highlights: Mediterranean spotted fever is a rickettsial infection caused by Rickettsia conorii . Infection occurs after the bite of an infected Rhipicephalus sanguineus tick. Focal neurological manifestations are rare and poorly described in the literature. This case highlights the management of peripheral facial palsy associated with infection. Abstract: Mediterranean spotted fever (MSF) caused by the bacterium Rickettsia conorii is one of the oldest known tick-borne diseases. It is transmitted by the brown dog tick Rhipicephalus sanguineus and occurs mainly in the Mediterranean area. MSF usually presents with a skin rash, high fever, and characteristic eschar at the site of the tick bite. The course of this disease may be benign or life-threatening. Focal neurological manifestations are unusual. We report the case of a patient who presented with an isolated peripheral facial nerve palsy complicating R conorii conorii infection.